The role of PET/CT in determining egfr mutation and ALK rearrangement in patients with lung adenocarcinoma (Annals of Medical Research, 2021)
Aim: The aim of the present study is to evaluate the role of tumor FDG uptake in a non-invasive method and the use of positron emission tomography / computed tomography (PET/CT) in estimating epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) rearrangements in cases of adenocarcinoma of the lung.Material and Methods: A total of 115 patients with the diagnosis of an adenocarcinoma of the lung that underwent F-18 FDG PET/CT for staging and whose EGFR mutation and ALK rearrangement status were analyzed were retrospectively analyzed. The association of the PET parameters (SUVmax, SUVmean, MTV and TLG) of primary tumor with the molecular profile was analyzed.Results: EGFR mutations (EGFR+ group) and ALK rearrangements (ALK+ group) were found in 15 (13%) and 10 (8.7%) of 115 patients; and 90 patients (78.3%) had no EGFR mutation or ALK rearrangement (EGFR/ALK-). EGFR mutations were found to be significantly higher among the never-smoked group (p=0.009). No significant association was identified between the SUVmean, MTV and TLG values and EGFR mutations; however, patients with a low SUVmax value were found to have a significantly higher rate of EGFR mutation (p=0.034). No statistically significant differences were found between the ALK+ and ALK- group in terms of age, sex, cigarette smoking status, tumor stage, or PET parameters.Conclusion: Our study results suggest that a low SUVmax value in lung adenocarcinomas is associated with EGFR mutation, although the diagnostic efficacy is not high.
Keywords: Adenocarcinoma; non-small cell lung cancer; epidermal growth factor receptor mutation; anaplastic lymphoma kinase rearrangement; PET/CT; SUVmax